2017
DOI: 10.21474/ijar01/4097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Slaughter Capture Chase Duration Stress on Carcass and Meat Quality of Indigenous Chicken Reared Under Traditional System in Benin.

Abstract: The current study aims to evaluate the influence of the pre-slaughter capture chase duration stress on carcass and meat quality in local chicken of Benin. Sixty-four chickens of 6 to 7 months old divided into 4 flocks of 8 males and 8 females each reared under traditional system were used. Chickens of first group were not chased before slaughter. Whereas, chickens of the second, the third and the fourth groups were slaughtered respectively after 5 minutes, 10 minutes and 15 minutes of chase by 3 persons. Carca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
(15 reference statements)
3
4
0
Order By: Relevance
“…This result confirms the dimorphism between males and females, males are taller and larger than females. Similar results had been reported in several avian species in different studies conducted on local poultry populations of the species Gallus gallus, such as the effect of sex on the weights of the different components of the carcass [1,10,14,15]. Other authors have shown that in local chicken breeds, the females generally grew slower than males and rarely reached 1 kg of live weight at 20 weeks of age compared to the 1.2 kg of the roosters [16][17][18][19].…”
Section: Carcass Characteristics Of Goliath Chickens By Age At Slaugh...supporting
confidence: 87%
See 3 more Smart Citations
“…This result confirms the dimorphism between males and females, males are taller and larger than females. Similar results had been reported in several avian species in different studies conducted on local poultry populations of the species Gallus gallus, such as the effect of sex on the weights of the different components of the carcass [1,10,14,15]. Other authors have shown that in local chicken breeds, the females generally grew slower than males and rarely reached 1 kg of live weight at 20 weeks of age compared to the 1.2 kg of the roosters [16][17][18][19].…”
Section: Carcass Characteristics Of Goliath Chickens By Age At Slaugh...supporting
confidence: 87%
“…In addition, this study showed that the wishbone of females had a higher water-holding capacity than that of males. However, other studies did not find any difference in the water-holding capacity by sex of local chickens [ 14 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In poultry, transport, lairage and shackling are major causes of stress. With increasing transport duration, early postmortem pH decline is increasingly slower, whereas ultimate pH is higher [ 45 , 67 , 68 ]. During transport, the potential stressors include vibrations, truck movements, impacts, social disturbances and noise [ 69 ].…”
Section: Stress and Meat Qualitymentioning
confidence: 99%